CFD Based Airfoil Shape Optimization for Aerodynamic Drag Reduction - Khot, Mohammed Taha Shafiq (2012)
A Master of Science thesis in Mechanical Engineering by Mohammed Taha Shafiq Khot entitled, "CFD Based Airfoil Shape Optimization for Aerodynamic Drag Reduction," submitted in May 2012. Thesis advisor is Dr. Ali Jhemi . Available are both soft and hard copies of the thesis.